Towards a benefits dependency network for DevOps based on a systematic literature review. Issue 11 (3rd July 2018) - Jabbari, Ramtin; bin Ali, Nauman; Petersen, Kai; Tanveer, Binish
Abstract: DevOps as a new way of thinking for software development and operations has received much attention in the industry, while it has not been thoroughly investigated in academia yet. The objective of this study is to characterize DevOps by exploring its central components in terms of principles, practices and their relations to the principles, challenges of DevOps adoption, and benefits reported in the peer‐reviewed literature. As a key objective, we also aim to realize the relations between DevOps practices and benefits in a systematic manner. A systematic literature review was conducted. Also, we used the concept of benefits dependency network to synthesize the findings, in particular, to specify dependencies between DevOps practices and link the practices to benefits. We found that in many cases, DevOps characteristics, ie, principles, practices, benefits, and challenges, were not sufficiently defined in detail in the peer‐reviewed literature. In addition, only a few empirical studies are available, which can be attributed to the nascency of DevOps research. Also, an initial version of the DevOps benefits dependency network has been derived. The definition of DevOps principles and practices should be emphasized given the novelty of the concept. Further empirical studies are needed to improve the benefits dependency network presented in this study. Abstract : In this paper, we aim to realize the relations between DevOps practices and benefits in a systematic manner. We used the concept of benefits dependency network to synthesize the findings of the literature, in particular, to specify dependencies between DevOps practices and link the practices to benefits. Only a few empirical studies are available that can be attributed to the nascency of DevOps research. An initial version of the DevOps benefits dependency network has been derived.